Understanding the Alterations in Lipid Metabolism in NAFLD Progression: Current Trends and Future Directions - Mungamuri, Sathish Kumar; Sinha, Sukesh Narayan; Javvadi, Yamini (Critical reviews in oncogenesis, 2021)
Nonalcoholic fatty liver disease (NAFLD) is a pathological condition, wherein fat deposition exceeds the allowable limits of the healthy person. If the condition persists for a long time, the patient will eventually develop NASH (nonalcoholic steatohepatitis), which will probably lead to HCC (hepatocellular carcinoma). The incidence of NAFLD is rising at an alarming rate, and still there are no drugs approved by the U.S. Food and Drug Administration for this devastating health condition. To combat and treat NAFLD successfully, it is essential to understand how routine lipid metabolism in the liver is altered under these conditions. In this review, we discuss specifically during the NAFLD progression how the signaling pathways leading to excess fat accumulation in the liver are changed. We also address variations in the mechanisms underlying hepatic lipid uptake and changes in fatty acid oxidation mechanisms. We will also highlight the role of transcription factors and other lipolytic enzymes that stringently regulate the hepatic de novo lipolysis (DNL) and emphasize how they are altered during NAFLD progression. Finally, we will also touch upon how the lipid disposal from the liver goes wrong during the NAFLD progression. A comprehensive understanding of the changes in lipid metabolism is essential for developing successful therapies for NAFLD.